Parent Perspectives of an Evidence-Based Intervention for Children with Autism Served in Community Mental Health Clinics - Stadnick, Nicole A. (2012)
Research suggests that improvements to community mental health (CMH) care for children with autism spectrum disorders (ASD) are needed. Recent research examining the feasibility of training CMH therapists to deliver a package of evidence-based practice intervention strategies (EBPs) targeting challenging behaviors for school-age children with ASD offers initial support for such efforts to improve care. Specifically, quantitative data from a recent pilot study indicate that CMH therapists with limited ASD experience can deliver an EBP intervention with fidelity and perceive it as useful to their practice. Further, client attendance is high and children demonstrate improvement on standardized measures. To further understand the feasibility and impact of training CMH therapists to deliver EBPs, this mixed-methods study examined parent perspectives of the process and impact of outpatient psychotherapy for 13 parents of children ages 5–13 with ASD whose therapists were trained to deliver the EBP intervention. Results complement and expand previously reported quantitative data on psychotherapy process indicating that parents are highly involved in treatment for their children, perceive a strong therapeutic alliance with their children’s therapist, and highlight that treatment was different once therapists began delivering the intervention. Results also indicate themes related to parents’ perceptions of positive child and parent outcomes that provide important details on the specific gains that were observed during treatment. Study findings underscore the importance of parent perspectives in understanding the process and impact of implementing EBPs in CMH settings for families of children with ASD.